Analisis biometri kepiting bakau (Scylla serrata) yang ditangkap dari hutan mangrove untuk mendukung kegiatan penggemukan kepiting bakau di Kabupaten Gresik - Maulana, Andi Moh Roby; Armaansyah, Dimas; Safitri, Nur Maulida; Farikhah (Fishery Product Technology Study Program, Yudharta University, Pasuruan, 2023)
This study aims to analyze the biometry of mud crabs caught from mangrove forests to support the provision of kempongan for mud crab cultivators. The research was conducted in Pangkahwetan Village, Ujungpangkah District, Gresik Regency, using a descriptive method. Samples (n= 2,240) collected in the period March-July 2022 from local fishermen. The research variables were biometry, carapace width frequency distribution, condition factor (C), ratio of male and female crabs, and maturity level of mud crabs. Data were analyzed using Microsoft Excel 2013. The sex ratio of crabs caught per month was analyzed by t-test (α=5%). The results of this study obtained a higher male sex ratio (88%) compared to females (12%) in the period March - July, 2022. Mud crab maturity based on the frequency distribution of female crab carapace width was 23.8% (March) , 24.1% (April), 61.5% (June), and 45.8% (July) while male crabs 6.2% (March), 2.9% (April), 6.3% (June ), and 8.2% (July). Male crabs are dominated by thin conditions and female crabs are dominated by fat conditions. The male and female crabs were statistically significantly different. The different conditions between male and female crabs obtained in this study indicate the need for separate management between male and female crabs when used as kempongan in a crab fattening business.